2022
DOI: 10.1039/d2ta00652a
|View full text |Cite
|
Sign up to set email alerts
|

Design of 3D topological nodal-net porous carbon for sodium-ion battery anodes

Abstract: Based on first-principles calculations, we propose a new 3D topological nodal-net carbon allotrope consisting of graphene nanoribbons. This structure possesses orthorhombic symmetry with 46 carbon atoms in its primitive cell,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…To find viable solutions to the aforementioned problems, several academic groups have proposed that integrating flexible carbon sheets into three-dimensional (3D) allotropes ensures fast sodium ion diffusion through one-dimensional (1D) periodic porous channels, high storage capacity due to the nonequivalent adsorption sites, excellent structural stability against the sodiation/desodiation process, and feasible synthesis process. This notion was stimulated due to the successful synthesis process of the direct assembly of graphene nanosheets into 3D metallic porous architecture using chemical vapor deposition (CVD) or the template method. , For example, metal–organic frameworks have been employed as ideal templates for preparing advanced negative electrode materials, which can be used to accommodate the large sodium ions. , Moreover, Xu et al prepared high-quality 3D porous reduced graphene foam, and their results showed that it offered an initial reversible Na + storage capacity of 836.2 mA h g –1 . Another study reported that defective C-honeycomb, constructed by the direct assembly of graphene nanoribbons, offers a gravimetric capacity of 711 mA h g –1 , but with high volume expansion (15%).…”
Section: Introductionmentioning
confidence: 99%
“…To find viable solutions to the aforementioned problems, several academic groups have proposed that integrating flexible carbon sheets into three-dimensional (3D) allotropes ensures fast sodium ion diffusion through one-dimensional (1D) periodic porous channels, high storage capacity due to the nonequivalent adsorption sites, excellent structural stability against the sodiation/desodiation process, and feasible synthesis process. This notion was stimulated due to the successful synthesis process of the direct assembly of graphene nanosheets into 3D metallic porous architecture using chemical vapor deposition (CVD) or the template method. , For example, metal–organic frameworks have been employed as ideal templates for preparing advanced negative electrode materials, which can be used to accommodate the large sodium ions. , Moreover, Xu et al prepared high-quality 3D porous reduced graphene foam, and their results showed that it offered an initial reversible Na + storage capacity of 836.2 mA h g –1 . Another study reported that defective C-honeycomb, constructed by the direct assembly of graphene nanoribbons, offers a gravimetric capacity of 711 mA h g –1 , but with high volume expansion (15%).…”
Section: Introductionmentioning
confidence: 99%
“…The nonzero independent elastic constants of this orthorhombic system are calculated to be C 11 = 172.56 GPa, C 22 = 181.82 GPa, C 33 = 137.23 GPa, C 12 = 37.57 GPa, C 13 = 33.34 GPa, C 23 = 41.04 GPa, C 44 = 41.81 GPa, C 55 = 36.33 GPa, and C 66 = 42.21 GPa. These elastic constants fully satisfy the Born–Huang criteria 39 for an orthorhombic system, 40 which require C ii > 0 ( i ∈ [1, 6]∩), C ii + C jj − 2 C ij > 0 ( i < j ; i , j ∈ [1, 3]∩), and C 11 + C 22 + C 33 + 2( C 12 + C 13 + C 23 ) > 0. Thus, cco-Si 48 is mechanically stable.…”
Section: Resultsmentioning
confidence: 91%
“…In Fig. 2a, we evaluated the cohesive energy of Zeo-C in comparison with those of several other 2D materials such as graphene, 46 graphyne, 47 graphenylene, 48 tC 24 , 49 and tC 8 . 50 The cohesive energy of Zeo-C is −8.664 eV per atom to exhibit sub-stability since the energy stability revealed is inferior to those of graphene (−9.224 eV per atom), tC 24 (−9.014 eV per atom), and tC 8 (−8.866 eV per atom).…”
Section: Resultsmentioning
confidence: 99%